Petumbuhan Ekonomi Provinsi Daerah Khusus Ibukota (DKI) Jakarta Dalam Pengaruh Teknologi Informasi - Ambar Tri Hapsari (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
The presence of technology is able to overcome technical deficiencies in producing more output with the same amount of input or producing output of high quality and quantity. We can see the influence of technology very clearly in various fields, namely by increasing capital productivity, labor productivity and total productivity. Thus, one way to continue increasing economic growth in DKI Province is by improving technology. The aim of this research is to analyze the influence of technology on the economic growth of DKI Province. This research uses secondary data for the period 1990-2000 obtained from government institutions. With the independent variable, namely technology which is measured through capital per workforce. This data was analyzed using the Ak model of Solow growth and estimated using the Ordinary Least Square Adjusted (OLS) method. The research results show that technology has a positive and significant effect on economic growth at a confidence level of 96.3 percent with a significance level of α=0.04. The determinant coefficient of this model is 0.9629, this means that 96 percent of the independent variable, namely technology (k), can explain the dependent variable, the remaining 4.82 percent can be explained by other variables outside this model. By knowing the benefits of technology which is very influential in economic growth, it is very important for the DKI Provincial government to take the best policies in maintaining and improving continuous technological progress through science by continuing to improve compulsory school programs and improving the quality of education, providing educational scholarships to finance schools and improving health.